Elementary school students computational thinking skills in learning-based 3D-Geometry problem - Widodo, Suprih; Cilviani, Cindy; Rahayu, Puji; Ramarumo, Tshepo (IndoMath: Indonesia Mathematics Education, 2023)
This study aims to investigate how elementary school students' computational thinking skills in learning 3D Geometry. The research method used was quasi-experimental with a pure post-test design of the 31 elementary school students selected using a purposive technique- sampling. Constructive, content and empirically validated calculus tests served as research tools. According to the results of this study, the computational thinking skills of elementary school students were greatly improved by learning from 3D-Geometry problems, and the average score was ranked high at 67.48 points. In this way, learning based on 3D-Geometry problems can be applied to the development of computational thinking skills in elementary school students.